KOORDINASI ANTAR LEMBAGA DALAM PENANGANAN PENYAKIT MASYARAKAT DI KECAMATAN UJUNG BATU TAHUN 2015 - Koharlan, Randi; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The title of this research is Inter-Institutional Coordination in the Implementation of Regional Regulation No. 1 of 2009 concerning Prohibition and Control of Community Disease in Ujung Batu Sub-District. The appearance of dimly lit stalls in Ujung Batu District resulted in an act that was prohibited by the norms and customs that prevailed in the community, namely the practice of prostitution in dimly lit stalls in Ujung Batu District, this involved three agencies namely the Ujung Batu District Government , Rokan Hulu Regency Police and Satpol PP to coordinate over community diseases or prostitution practices in Ujung Batu District and the factors that influence it. The theoretical concept that researchers use is coordination according to Henry Fayol, which explains several indicators, namely communication, cooperation, division of tasks, meetings and meetings while the factors that influence it are based on research found in the field. The research method used in this study is a qualitative descriptive method. where in this study, the researcher tried to explain the coordination between three institutions, namely the Ujung Batu District Government, Ujung Batu Police Station and the Rokan Hulu Regency Satpol. The results of this study concluded that the Inter-Institutional Coordination in the Implementation of Local Regulation No. 1 of 2009 concerning Prohibition and Control of Community Disease in Ujung Batu District can be concluded that the Inter-Institutional Coordination in the Implementation of Regional Regulation No. 1 of 2009 concerning Prohibition and Control of Community Disease in Ujung Batu District is quite good . And the factors that influence it are unclear coordination schedules and lack of public awareness. Keywords: Coordination, Institution, Community Disease, Regional Regulation Number 1 of 2009.